On-line and Adaptive Load Blinding Protection Scheme to Resolve Protection Limits in Networks with Highly Integrated DERs - Ganjavi, Reza; Scoble, Colin; Dantas, Rui; Yazadzhiyan, Boris; Kasap, Hakan; Hann, Sebastian; Meyer, Janick; Jäger, Johann; et al. (27th International Conference on Electricity 2023, 2023)
This paper investigates the challenges that directional overcurrent protection equipped with Load blinding function observes at parallel transformers linking 132kV and 33kV distribution levels in UK Power Networks. With the increase of reverse power flow, the directional overcurrent protection (DOC) at 132/33kV transformers could mal-operate if the reverse power flow exceeds the DOC current threshold. The application of a Load blinding protection scheme at the DOC protection is already well investigated in literature [3,4,5,6] to propose solutions with static protection settings aiming to increase reverse power flow at parallel Grid transformers (132/33kV) and Primary (33/11kV) distribution transformers. These static settings are challenged to be maloperation free in the future network with bi/multidirectional active and reactive power flow and Distributed Energy Resource (DER) generation with complex operational behaviour regarding fault current and negative sequence current contribution.
CRIS-Team Scopus Importer:2024-12-16